(untitled) (Medical Forum Monthly, 2024)
Objective: To identify and assess the risk factors associated with epidural failure during cesarean section anesthesia. Study Design: Prospective study Place and Duration of Study: This study was conducted at the Anesthesia, Lady Reading Hospital, Peshawar November 2022 to October, 2023. Methods: A total of 400 patients were included in the study. In 2022, at Lady reading Hospital, Peshawar. Data of patients who had cesarean sections with epidural anesthesia (EA) and catheterization were collected. EA failure was identified as the need for intravenous anesthetics during the cesarean section, resulting in conversion to general anesthesia (GA). Results: Most of the epidural failure patients 82.5% was applied method of loss of resistance to air. Further, catheter depth, resident, obstetric anesthesiologist, emergency surgery, rupture of membrane and parity in epidural failure and non-failure patients were almost equal, (p>0.050). Whereas, the mean waiting time in epidural failure patients was less than the non-failure patients as13.23±2.19 minutes and 15.22±3.38 minutes, respectively. Conclusion: Patients who have a previous epidural catheterization, experience inadequate waiting time, and are younger in age may face a higher risk of epidural analgesia (EA) failure. Specifically, the risk of EA failure increases by 2.6-fold for individuals with a previous epidural catheterization compared to those without catheterization history.